1989
DOI: 10.5547/issn0195-6574-ej-vol10-no4-9
|View full text |Cite
|
Sign up to set email alerts
|

Technological Innovation and a Changing Energy Mix - A Parametric and Flexible Approach to Modeling Ontario Manufacturing

Abstract: For the purposes of explaining historical trends in relative fuel usage and energy efficiency, an encompassing framework must incorporate both the influence of changing fuel prices and technological change. Schurr (1982), Rosenberg (1983), Jorgenson (1984, 1986) and Berndt (1986) have provided recent documentation of the importance of these two factors in explaining productivity growth. Moreover, these studies indicate that a key to understanding such trends is analysis at the individual industrial sector leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…They find that technological change leads to savings in both fuels and electricity. In a similar study, Mountain, Stipdonk, and Warren (1989) find that technological change in Ontario manufacturing industries is oil-saving and natural gas-using. Results for electricity use depended on the industry.…”
Section: A Studies Of Energy Consumption Across Timementioning
confidence: 88%
“…They find that technological change leads to savings in both fuels and electricity. In a similar study, Mountain, Stipdonk, and Warren (1989) find that technological change in Ontario manufacturing industries is oil-saving and natural gas-using. Results for electricity use depended on the industry.…”
Section: A Studies Of Energy Consumption Across Timementioning
confidence: 88%
“…69 Mountain et al (1989) attempted to assess the effects of relative prices on relevant technology diffusion in the Ontario manufacturing sector from 1962 to 1984. They found that fuel choices changed in response to changes in fuel prices, but given the nature of their analysis, they could not distinguish between product substitution and technology diffusion.…”
Section: Empirical Analysesmentioning
confidence: 99%
“…Very recently, Popp et al (2009) prepared an excellent review scrutinizing the role of technological change on environmental economics for the forthcoming Handbook of Economics of Technical Change. In this review, some significant works cited in conjunction with the relationships among innovation (technological change), EE, and ES are Mountain et al (1989), Sterner (1990), Berndt et al (1993), Newell et al (1999, Popp (2001), Nijkamp et al (2001), Popp (2002), Mulder et al (2003, Anderson and Newell (2004), Linn (2008), and Sue Wing (2008. Some of the conclusions of these works are i) the technology is energy saving; ii) energy patents leads to long-run energy savings; iii) science and technology (S&T) takeoff should have an energy-saving bias resulting in lower energy prices, however, this leads to more economic growth and greater energy consumption by households, so that the net effect of the S&T takeoff is greater energy use and more emissions; iv) increase in the price of energy leads to technology adoption that negligibly reduces energy demand; v) energy prices and regulatory standards affect EE-related innovation; and vi) economic barriers affect adoption of EE technology more than financial and uncertainty barriers.…”
Section: /21mentioning
confidence: 99%